Correlations between prescription opioid analgesic dispensing levels and related mortality and morbidity in Ontario, Canada, 2005–2011. (21st November 2013) - Fischer, Benedikt; Jones, Wayne; Urbanoski, Karen; Skinner, Roger; Rehm, Jürgen
Abstract Introduction and Aims Prescription opioid analgesic (POA)‐related harms constitute a major public health problem in North America. Ontario features above‐average POA use levels in Canada and has seen consistent increases in related mortality and morbidity. Recent studies documented strong correlations between POA dispensing levels and related harm outcomes on population levels. We examined correlations between POA dispensing and key POA‐related mortality and morbidity indicators in Ontario, 2005–2011. Design and Methods Correlations between (i) annual dispensing levels of four strong POA formulations (fentanyl, hydromorphone, morphine and oxycodone; from IMS Brogan's Compuscript converted to defined daily doses) and POA‐related mortality (based on provincial coroner's data) and (ii) annual total POA dispensing and POA‐related treatment caseload (from the Drug and Alcohol Treatment Information System) were examined for the study context. Results Strong and significant correlations were observed between POA dispensing and mortality for three formulations, namely hydromorphone: 0.98 [95% confidence interval (CI) 0.89–1.00; P < 0.001], fentanyl: 0.93 (95% CI 0.58–0.99; P = 0.003) and oxycodone: 0.93 (95% CI 0.57–0.99; P = 0.003), but not morphine (−0.29; 95% CI−0.86–0.59; P = 0.523), as well as for treatment when examining congruent years [0.99 (95% CI 0.92–1.00); P < 0.001] and when using a 1‐year offset (1.00; 95% CI 0.96–1.00; P < 0.001). Discussion and Conclusions POA dispensing levels were found to be strongly correlated with mortality and morbidity (treatment) indicators. Targeted and sensible reductions of POA use level would likely constitute a primary measure to reduce POA‐related harms on a population level, especially in a jurisdiction with high POA consumption levels. [Fischer B, Jones W, Urbanoski K, Skinner R, Rehm J. Correlations between prescription opioid analgesic dispensing levels and related mortality and morbidity in Ontario, Canada, 2005–2011. Drug Alcohol Rev 2014;33:19–26]